2023
DOI: 10.1002/celc.202201149
|View full text |Cite
|
Sign up to set email alerts
|

General Concepts and Recent Advances in the Electrochemical Transformation of Chloro‐ and Hydrosilanes

Abstract: Organosilanes play an important role in organic synthesis as well as in a variety of further areas, ranging from life science to transportation. Especially, the electrochemical access has become increasingly important in the past years and developed into an essential topic due to new conceptual approaches and mediated reaction control. With the commercial availability of high‐quality electrochemical equipment, the technical requirements for electro‐conversion are at hand to a wide audience. This results in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 221 publications
(675 reference statements)
0
5
0
1
Order By: Relevance
“…In general, substituents at the metaposition of the aromatic aldehydes give higher enantioselectivity than ortho-and para-substituents, and the electronic properties of substituents have little impact on both yields and ee values. The functional group tolerance is also broad with respect to the aldehyde coupling partner, including aryl halides (30,40,41,43, and 44), ethers (32,33,34,35,3,46, and 47), thioethers (36), heterocycles (38,45), and esters (46, 47). It is worth noting that in the case of a substrate bearing a remote stereocenter, the stereochemistry in the products was fully controlled by the stereochemistry of ligands (L7, ent-L7) rather than that of the substrate (46, 47).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, substituents at the metaposition of the aromatic aldehydes give higher enantioselectivity than ortho-and para-substituents, and the electronic properties of substituents have little impact on both yields and ee values. The functional group tolerance is also broad with respect to the aldehyde coupling partner, including aryl halides (30,40,41,43, and 44), ethers (32,33,34,35,3,46, and 47), thioethers (36), heterocycles (38,45), and esters (46, 47). It is worth noting that in the case of a substrate bearing a remote stereocenter, the stereochemistry in the products was fully controlled by the stereochemistry of ligands (L7, ent-L7) rather than that of the substrate (46, 47).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a recent review, Waldvogel notes the challenges of CV studies of silyl halides being due to their facile hydrolysis to generate HCl. 38 We have previously reported that the combination of TDAE and silyl halides induces reductive decarboxylation of NHP esters but that TDAE/TESCl was determined to reduce benzylic NHP esters at rates that are slow relative to other silyl halides. 39 No significant current increase were observed upon addition of aldehyde 1 (100 equiv) to TDAE 2+ (PF 6 − ) 2 [Figure 4C(viii)].…”
Section: ■ Mechanistic Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Der Lin-Gruppe gelang elektrochemisch, was als schwierig 32) gilt: Si-Si-Bindungen zu bilden. 33) ) wurden von Gooßen und Waldvogel an Bor-dotierten Dia mant elektro den in Konzentrationen bis zu 0,85 mol L -1 erhalten.…”
Section: Elektrosyntheseunclassified
“…Such an approach often leads to significantly improved chemoselectivity and efficiency in the process. Moreover, exploring electrochemical methods, which are attracting growing interest in the scientific community, [75][76][77] would offer another intriguing avenue. In his pioneering research, Jouikov showcased the feasibility of silylating alkynes with chlorosilane.…”
Section: From Halosilanes or Silyl Triflatesmentioning
confidence: 99%